POLA PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH MEBEL DAN UKIR SEBAGAI MOTOR PENGGERAK EKONOMI KERAKYATAN DI KABUPATEN JEPARA - DWI RETNA SULISTYAWATI; SARWIDO SARWIDO (Jurnal DISPROTEK, 2010)
Abstract Growth of small and middle furniture and carving industry represent a commitment which need to be placed forward in framework to race growth and generalization of economics in all subprovince region ofJepara as especial encoding materialization of economics base on nationality. Identify potency resource, problem, opportunity, and challenge faced need to be conducted by a systematic and consistent, and framework compiles a direction and policy of growth of small and medium furniture and carving industry in sub-prdvince of Jepara. Area autonomy becomes activator to compile pattern growth of small and medium furniture and carving industry according to society aspiration. Globalization is viewed as well-balanced opportunity to set Jepara as supplier commodity of furniture and carving industry becomes bigger part product of small and middle industry. The growth Pattern content covers direction, planning program, strategic and also consistent policy with riel requirement and materialization of economics base on nationality. The activities are begun with by descriptive research about quantitative and qualitative condition middle and small furniture and carving industry in sub-province region ofJepara. Portrait small and middle Industrial will be identified by key factor and success with analysis of SWOT (Strength, Weaknesses, Opportunities, Treats)